Service Cultures, Personalities, and the Struggle to Establish a Joint Headquarters in Halifax during the Second World War - Goette, Richard (The Northern Mariner / Le marin du nord, 2024)
The Royal Canadian Air Force (RCAF) and Royal Canadian Navy (RCN) sought to emulate their British counterparts in joint defence of convoys. However, a strange omission was the inability of Canadian aviators and sailors to come together in a joint headquarters in Halifax until July 1943 – fully five years after the British and one year after the United States. Why was this so? Many factors account for this failure. They include resource constraints, physical location issues, and communications systems considerations. However, the most important factors were service culture and individual personalities, notably conceptions regarding air-naval jointness and command and control. L’Aviation royale canadienne et la Marine royale canadienne cherchaient à imiter leurs homologues britanniques dans la défense conjointe des convois. Cependant, l’incapacité des aviateurs et des marins canadiens à se réunir dans un quartier général interarmées à Halifax avant juillet 1943, cinq ans après la Grande-Bretagne et un an après les États-Unis, semblait des plus étranges. Pourquoi en était-il ainsi? De nombreux facteurs expliquent cet échec, notamment les contraintes au niveau des ressources, les questions d’emplacement physique et les considérations relatives aux systèmes de communication. Pourtant, les facteurs les plus importants étaient la culture de service et les personnalités individuelles, notamment les conceptions de l’interarmisation de l’armée et de la marine, le commandement et le contrôle.